Halving Poverty in Russia by 2024 : What Will It Take? - World Bank Group (World Bank, Washington, DC, 2018)
We identify the conditions in terms of economic growth and public transfers required to “…reduce poverty in the Russian Federation by one half by 2024” as stated in President Putin’s Decree of May 17th, 2018. The current poverty rate is 13.2 percent, and halving it would mean reducing the current rate to 6.6 percent by 2024. We estimate that average annual growth of 1.5 percent would bring down the poverty rate from 13.2 percent to only 10.7 percent by 2024. And even if Russia were to be able to catch up with the rest of the world, and grow at 3.2 percent annually, the poverty rate would fall to 8.1 percent – still below the stated goal of 6.6 percent. Consequently, to reach the Presidential target of 6.6 percent, we estimate that the annual required growth rate would need to surge to 4.4 percent.